A single dose of cannabidiol increases ad libitum energy intake in healthy adults but does not affect postprandial glucose or lipid metabolism - Drusus A. Johnson; Mark P. Funnell; Thomas G. Cable; Donald Peden; Chris J. McLeod; Patrick C. Wheeler; Stephen J. Bailey; Tom Clifford; Liam M. Heaney; Lewis J. James (Appetite, 2026)

Next steps in dehydration and endurance exercise performance research: exploring participant-relevant factors - Mark P. Funnell; Thomas G. Cable; Heather Z. Macrae; Lewis J. James (European Journal of Applied Physiology, 2026)

First record of a piebald leucistic smallspotted catshark Scyliorhinus canicula in a special area of conservation, UK - Neil D. Cook; Sarah L. Perry; Declan T. G. Quigley; Jo Cable; Sarah E. Perkins (Marine Biodiversity, 2025)
Colour aberrations are widely reported in vertebrates, but seldom for elasmobranchs. Shark trophic level varies ontogenetically and according to species, so atypical colouration may have implications for ecological fitness both as predator and prey. Here, we present, to our knowledge, the first and only record of a piebald leucistic smallspotted catshark Scyliorhinus canicula from Welsh waters, specifically in the Cardigan Bay Special Area of Conservation, UK. This adds to the five previous observations from the Irish and Mediterranean Seas. Sharks face numerous threats, including the physiological impacts of climate change. In this context, the prevalence and implications of leucism remain a knowledge gap.

P30-27 A non-animal safety assessment framework for systemic, reproductive and developmental toxicity - M. Dent; S. Cable; P. Carmichael; P. Kukic; S. Malcomber; I. Muller; A. Punt; G. Reynolds; J. Reynolds; S. Scott; A. White; K. Wolton; et al. (Toxicology Letters, 2025)

7 days of L-citrulline supplementation does not improve running performance in the heat whilst in a hypohydrated state - Thomas G. Cable; Mark P. Funnell; Kirsty M. Reynolds; Ella F. Hudson; Heather Z. Macrae; Drusus A. Johnson; Lee Taylor; Liam M. Heaney; Stephen A. Mears; Stephen J. Bailey; Lewis J. James (European Journal of Applied Physiology, 2025)
Purpose 7 days L-citrulline supplementation has been reported to improve blood pressure, $$\mathop {\text{V}}\limits^{.}$$ V . O 2 kinetics, gastrointestinal (GI) perfusion and endurance cycling performance through increasing arterial blood flow. In situations where blood volume is compromised (e.g., hyperthermia/hypohydration), L-citrulline may improve thermoregulation and exercise performance by redistributing blood flow to aid heat loss and/or muscle function. This study assessed 7 days L-citrulline supplementation on running performance in the heat, whilst mildly hypohydrated. Methods 13 endurance runners (2 female, 31 ± 8 y, $$\mathop {\text{V}}\limits^{.}$$ V . O 2 peak 60 ± 6 mL/kg/min) participated in a randomised crossover study with 7 days L-citrulline (CIT; 6 g/d) or placebo (maltodextrin powder; PLA) supplementation. Participants completed a 50 min running ‘preload’ at 65% $$\mathop {\text{V}}\limits^{.}$$ V . O 2 peak (32 °C, 50% relative humidity) to induce hyperthermia and hypohydration before a 3 km running time trial (TT). Body mass and blood samples were collected at baseline, pre-preload, post-preload and post-TT, whilst core and skin temperature, heart rate and perceptual responses were collected periodically throughout. Results TT performance was not different between trials (CIT 865 ± 142 s; PLA 892 ± 154 s; P = 0.437). Core and skin temperature and heart rate ( P ≥ 0.270), hydration (sweat rate, plasma volume, osmolality) indices ( P ≥ 0.216), GI damage ( P ≥ 0.260) and perceptual responses ( P ≥ 0.610) were not different between trials during the preload and TT. Conclusions 7 days of L-citrulline supplementation had no effect on 3 km running performance in the heat or any effects on thermoregulation or GI damage in trained runners in a hypohydrated state.

P19-11 Establishing scientific confidence in a NAM toolbox and workflow using a flexible framework - M.T. Baltazar; G. Reynolds; M. Dent; P.L. Carmichael; P. Kukic; S. Malcomber; A. Middleton; K. Przybylak; A. Punt; J. Reynolds; S. Scottt; A. White; et al. (Toxicology Letters, 2024)

P01-01 A review of in silico and in vitro methods for use in a risk assessment of a substance acting via oestrogen or androgen modalities - K. Roylance; R. Brown; G. Panter; O. Tran; O. Green; A. Riu; A. Giusti; A. Loisy; C. Choi; D. Bury; D. Lange; J. Naciff; et al. (Toxicology Letters, 2024)

OS01-08 Assessing the protectiveness and utility of a new approach methodology-based toolbox for systemic toxicity - M. Dent; M. Baltazar; S. Cable; P. Carmichael; S. Hatherell; P. Kukic; S. Malcomber; A. Middleton; A. Punt; G. Reynolds; J. Reynolds; S. Scott; et al. (Toxicology Letters, 2024)

Liquid phase detection in the miniature scale. Microfluidic and capillary scale measurement and separation systems. A tutorial review - Cable G. Warren; Purnendu K. Dasgupta (Analytica Chimica Acta, 2024)

Using fish models to investigate the links between microbiome and social behaviour: The next step for translational microbiome research? - Marta C. Soares; Jo Cable; Monica G. Lima‐Maximino; Caio Maximino; Raquel Xavier (Fish and Fisheries, 2019)
Recent research has revealed surprisingly important connections between animals’ microbiome and social behaviour. Social interactions can affect the composition and function of the microbiome; conversely, the microbiome affects social communication by influencing the hosts’ central nervous system and peripheral chemical communication. These discoveries set the stage for novel research focusing on the evolution and physiology of animal social behaviour in relation to microbial transmission strategies. Here, we discuss the emerging roles of teleost fish models and their potential for advancing research fields, linked to sociality and microbial regulation. We argue that fish models, such as the zebrafish ( Danio rerio , Cyprinidae), sticklebacks (‎Gasterosteidae), guppies (Poeciliidae) and cleaner–client dyads (e.g., obligate cleaner fish from the Labridae and Gobiidae families and their visiting clientele), will provide valuable insights into the roles of microbiome in shaping social behaviour and vice versa, while also being of direct relevance to the food and ornamental fish trades. The diversity of fish behaviour warrants more interdisciplinary research, including microbiome studies, which should have a strong ecological (field‐derived) approach, together with laboratory‐based cognitive and neurobiological experimentation. The implications of such integrated approaches may be of translational relevance, opening new avenues for future investigation using fish models.

Half the story: Thermal effects on within‐host infectious disease progression in a warming climate - Alexander Stewart; Pascal I. Hablützel; Martha Brown; Hayley V. Watson; Sophie Parker‐Norman; Anya V. Tober; Anna G. Thomason; Ida M. Friberg; Joanne Cable; Joseph A. Jackson (Global Change Biology, 2018)
Immune defense is temperature dependent in cold‐blooded vertebrates ( CBV s) and thus directly impacted by global warming. We examined whether immunity and within‐host infectious disease progression are altered in CBV s under realistic climate warming in a seasonal mid‐latitude setting. Going further, we also examined how large thermal effects are in relation to the effects of other environmental variation in such a setting (critical to our ability to project infectious disease dynamics from thermal relationships alone). We employed the three‐spined stickleback and three ecologically relevant parasite infections as a “wild” model. To generate a realistic climatic warming scenario we used naturalistic outdoors mesocosms with precise temperature control. We also conducted laboratory experiments to estimate thermal effects on immunity and within‐host infectious disease progression under controlled conditions. As experimental readouts we measured disease progression for the parasites and expression in 14 immune‐associated genes (providing insight into immunophenotypic responses). Our mesocosm experiment demonstrated significant perturbation due to modest warming (+2°C), altering the magnitude and phenology of disease. Our laboratory experiments demonstrated substantial thermal effects. Prevailing thermal effects were more important than lagged thermal effects and disease progression increased or decreased in severity with increasing temperature in an infection‐specific way. Combining laboratory‐determined thermal effects with our mesocosm data, we used inverse modeling to partition seasonal variation in Saprolegnia disease progression into a thermal effect and a latent immunocompetence effect (driven by nonthermal environmental variation and correlating with immune gene expression). The immunocompetence effect was large, accounting for at least as much variation in Saprolegnia disease as the thermal effect. This suggests that managers of CBV populations in variable environments may not be able to reliably project infectious disease risk from thermal data alone. Nevertheless, such projections would be improved by primarily considering prevailing thermal effects in the case of within‐host disease and by incorporating validated measures of immunocompetence.

Antecedent Conditions Influence Soil Respiration Differences in Shrub and Grass Patches - Jessica M. Cable; Kiona Ogle; Greg A. Barron-Gafford; Lisa P. Bentley; William L. Cable; Russell L. Scott; David G. Williams; Travis E. Huxman (Ecosystems, 2013)

Lack of relationship between sedentary behaviour and vascular function in children - Nicola Hopkins; G. Stratton; N. D. Ridgers; L. E. F. Graves; N. T. Cable; D. J. Green (European Journal of Applied Physiology, 2012)

Impact of exercise training on endothelial function and body composition in young people: a study of mono- and di-zygotic twins - N. D. Hopkins; G. Stratton; N. T. Cable; T. M. Tinken; L. E. F. Graves; D. J. Green (European Journal of Applied Physiology, 2012)

Does brachial artery flow-mediated dilation scale to anthropometric characteristics? - N. D. Hopkins; D. J. Green; T. M. Tinken; L. Sutton; N. McWhannell; N. T. Cable; G. Stratton; K. George (European Journal of Applied Physiology, 2010)

Microsatellite markers for the proboscis monkey (Nasalis larvatus) - M. Salgado-Lynn; D. W. G. Stanton; R. Sakong; J. Cable; B. Goossens; M. W. Bruford (Conservation Genetics Resources, 2010)

Antagonistic interactions between garden yeasts and microfungal garden pathogens of leaf-cutting ants - Andre Rodrigues; Rachel N. Cable; Ulrich G. Mueller; Maurício Bacci; Fernando C. Pagnocca (Antonie van Leeuwenhoek, 2009)

Soil Texture Drives Responses of Soil Respiration to Precipitation Pulses in the Sonoran Desert: Implications for Climate Change - Jessica M. Cable; Kiona Ogle; David G. Williams; Jake F. Weltzin; Travis E. Huxman (Ecosystems, 2008)

Episodic high intensity mixing events in a subterranean estuary: Effects of tropical cyclones - Christopher G. Smith; Jaye E. Cable; Jonathan B .Martin (Limnology and Oceanography, 2008)
Hydrostatic balances between fresh and saline groundwater and saline surface water control the physical and chemical framework of subterranean estuaries, but they are responsive to high frequency (waves and tides), low frequency (seasonal recharge patterns), and episodic (storm) events. In this study, we document a salinity and pressure perturbation to the subterranean estuary in east‐central Florida during and after the passage of Tropical Storm Tammy on 04 Oct 2005–05 Oct 2005 and Hurricane Wilma on 24 Oct 2005. These storms reversed hydraulic gradients, forced lagoon water into the aquifer, and shifted the outflow face landward. Salinity at 1.5 m and 2.5 m below a common datum converged on similar values intermediate between fresh and lagoon water salinities. The outflow face reestablished pre‐storm conditions after 80 days at 15 m offshore, but more than 160 days at 30 m offshore, confirming that both the flow field and fluid sources control the position of the subterranean estuary. Episodic, high intensity events could influence the biogeochemical setting of the subterranean estuary and the overlying water body by altering redox conditions in the subterranean estuary during the landward migration of the dispersive mixing zone, increasing short‐term discharge of potentially contaminated groundwater, and/or changing pore fluid residence time within the seepage face and along the mixing zone‐seepage face front.

The effect of acute simulated moderate altitude on power, performance and pacing strategies in well-trained cyclists - Sally A. Clark; P. C. Bourdon; W. Schmidt; B. Singh; G. Cable; K. J. Onus; S. M. Woolford; T. Stanef; C. J. Gore; R. J. Aughey (European Journal of Applied Physiology, 2007)

Intraseasonal Variation in Water and Carbon Dioxide Flux Components in a Semiarid Riparian Woodland - Enrico A. Yepez; Russell L. Scott; William L. Cable; David G. Williams (Ecosystems, 2007)

Response of net ecosystem gas exchange to a simulated precipitation pulse in a semi-arid grassland: the role of native versus non-native grasses and soil texture - Travis E. Huxman; Jessica M. Cable; Danielle D. Ignace; J. Alex Eilts; Nathan B. English; Jake Weltzin; David G. Williams (Oecologia, 2004)

Polychlorinated Biphenyls and Chlordane in the Gonads of Paddlefish, Polyodon spathula, from the Ohio River - D. T. Gundersen; M. D. Krahling; J. J. Donosky; R. G. Cable; S. D. Mims (Bulletin of Environmental Contamination and Toxicology, 1998)